Sistem Informasi Penjualan Kartu dan Voucher Internet Berbasis Web Menggunakan Metode Waterfall - Muhammad Yusuf; Barany Fachri (Bulletin of Computer Science Research, 2024)
Currently, card and internet voucher sales at The One Ponsel Store are still done manually. This causes recording errors such as inaccurate stock and missed transactions, and results in long customer waiting times when the store is busy. Another disadvantage of this manual method is the difficulty of tracking sales and stock data in real-time, making it difficult for store managers to make quick and accurate decisions, which results in lost sales potential and operational efficiency. To overcome this problem, the application of web-based information technology is the right solution. The proposed card and voucher sales information system is designed to automate the entire business process, enabling more accurate inventory management, more efficient sales recording, and faster reporting. The Waterfall method was chosen because it provides a systematic framework in the analysis, design, implementation, and testing of the system so that it meets user needs. The results of system testing with Lighthouse showed high performance with scores: Performance 92, Accessibility 88, Best Practices 96, and SEO 90, indicating that the resulting information system is reliable and effective. This system significantly improves the efficiency of stock and sales management at The One Ponsel Store, reduces manual errors, and speeds up the customer service process, providing a positive impact on operations and customer satisfaction.